Contribution à l’étude des structures tectoniques responsables d’instabilité dans la carrière du gisement de fer d’Anini, W.de Sétif, Algérie - Amara,Saadia; BOUIMA ,T(Encadreur) (Université Ferhat Abbas Sétif 1. institut d'architecture et sciences de la terre. département de géologie, 2014)
The massif of Dj. Anini makes parity of the relative indigenous unit southern Sétifienne appearing in tectonic window which emerges under tablecloth tellienne of Djemila. It was represented by a unit of formation carbonated of age enomano – turonien the sector of Anini was dominated by so many accidents in the direction NNW-SSE which compartment the solid mass in various blocks and confer to theme a structure in horst and grabens. The mine Anini contain erriferous mineralization (hematite, goetite) associated walls of calcite and barite mineralization witch maintain the connection with a gravitational karst, but the origin of iron is still unknown today. The deposit is part of the small deposits ationwide, with its open pit operation that does not require large resources; it is one of the major iron-bearing deposits of the East, because of its high iron content. The release of the factors favoring the relaxation of blocks that preferably ould have a better opening of the northern quarry south countered that dip to the south, better recovery of ore at lower risk using small machines such as scales to make sure that ore could be recovered even small body
Keywords: Djebel Anini; La minéralisation; L’exploitation; Le fer